Angular-dependent magnetism in Co(001) single-crystal nanowires: capturing the vortex nucleation fields. Issue 45 (4th November 2016) - Montazer, A. H.; Ramazani, A.; Almasi Kashi, M.; Zavašnik, J.
Abstract : The analytical predictions on angular dependence of vortex nucleation field are realized in a weakly interacting Co(001) single-crystal nanowire system. Abstract : Experimental realization of analytically predicted behavior for nanoscale magnetic systems can pave the way for promoting synergistic research and has significant importance for applications and thorough understanding of nanomagnetism. Here, we report on the magnetism of a nearly ideal nanowire (NW) system, vertically aligned hcp-Co(001) single-crystal NWs electrochemically deposited inside an aluminum oxide template, as a function of the angle (0° ≤ θ ≤ 90°) between the magnetic field and the NW axis. Using high resolution transmission electron microscopy, detailed structural investigations on the few micrometers long and approximately 45 nm in diameter NWs exhibit crystalline inhomogeneities at the NW ends, evidencing magnetic localization in the single crystalline NWs. Using a vibrating sample magnetometer enabled us to extract different magnetic parameters, thereby evaluating angular dependence of magnetism in NW arrays and individual NWs. While the conventional hysteresis and first-order reversal curve (FORC) diagram methods show a monotonic decreasing and increasing behavior for coercivity as a function of θ, respectively, the average coercivity obtained from the irreversible distribution indicates a non-monotonic behavior, involving a complex magnetization reversal triggered by the propagation of vortex domain walls (DWs) and single vortex states for high field angles. Additionally, the hysteresis curve coercivity is phenomenologically parameterized at each θ based on the angular FORC (AFORC) measurements. Comparing the AFORC coercivities (varying between 5 kOe at θ = 0° and 9.3 kOe at θ = 90°) with absolute values of the angular dependence of the vortex nucleation field confirms an almost complete concurrence between experimental findings and analytical calculations on individual NWs. Consequently, our results show the first analytically supported evidence on capturing the nucleation fields and the occurrence of vortex DW propagation at each θ for weakly interacting Co NW arrays with a large magnetocrystalline anisotropy along the length.